A Novel Cell Type Enables B. subtilis to Escape from Unsuccessful Sporulation in Minimal Medium - Defeu Soufo, Hervé Joël (Frontiers in Microbiology, 2016)
Sporulation is the most enduring survival strategy developed by several bacterial species. However, spore development of the model organism Bacillus subtilis has mainly been studied by means of media or conditions optimized for the induction of sporogenesis. Here, I show that during prolonged growth during stationary phase in minimal medium, B. subtilis undergoes an asymmetric cell division that produces small and round-shaped, DNA containing cells. In contrast to wild-type cells, mutants harboring spo0A or spoIIIE/sftA double mutations neither sporulate nor produce this special cell type, providing evidence that the small round cells emerge from the abortion of endospore formation. In most cases observed, the small round cells arise in the presence of sigma H but absence of sigma F activity, different from cases of abortive sporulation described for rich media. These data suggest that in minimal media, many cells are able to initiate but fail to complete spore development, and therefore return to normal growth as rods. This work reveals that the continuation of asymmetric cell division, which results in the formation of the small round cells, is a way for cells to delay or escape from - unsuccessful - sporulation. Based on these findings, I suggest to name the here described cell type as “dwarf cells” to distinguish them from the well-known minicells observed in mutants defective in septum placement or proper chromosome partitioning.